Characterization of azo reduction activity in a novel ascomycete yeast strain - Ramalho, Patrícia A. (2004)
Several model azo dyes are reductively cleaved by growing cultures of an ascomycete yeast species, Issatchenkia occidentalis. In liquid media containing 0.2 mM dye and 2% glucose in a mineral salts base, more than 80% of the dyes are removed in 15 h, essentially under microaerophilic conditions. Under anoxic conditions, decolorization does not occur, even in the presence of pregrown cells. Kinetic assays of azo reduction activities in quasi-resting cells demonstrated the following: (i) while the optimum pH depends on dye structure, the optimum pH range was observed in the acidic range; (ii) the maximum decolorizing activity occurs in the late exponential phase; and (iii) the temperature profile approaches the typical bell-shaped curve. These results indirectly suggest the involvement of an enzyme activity in azo dye reduction. The decolorizing activity of I. occidentalis is still observed, although at a lower level, when the cells switch to aerobic respiration at the expense of ethanol after glucose exhaustion in the culture medium. Decolorization ceased when all the ethanol was consumed; this observation, along with other lines of evidence, suggests that azo dye reduction depends on cell growth. Anthraquinone-2-sulfonate, a redox mediator, enhances the reduction rates of the N,N-dimethylaniline- based dyes and reduces those of the 2-naphthol-based dyes, an effect which seems to be compatible with a thermodynamic factor. The dye reduction products were tested as carbon and nitrogen sources. 1-Amino-2-naphthol was used as a carbon and nitrogen source, and N,N-dimethyl-p-phenylenediamine was used only as a nitrogen source. Sulfanilic and metanilic acids did not support growth either as a carbon or nitrogen source.